The COVID‐19 pandemic and its consequences for chronic pain: a narrative review. (18th July 2022) - Shanthanna, H.; Nelson, A. M.; Kissoon, N.; Narouze, S.
Summary: The COVID‐19 pandemic transformed everyday life, but the implications were most impactful for vulnerable populations, including patients with chronic pain. Moreover, persistent pain is increasingly recognised as a key manifestation of long COVID. This narrative review explores the consequences of the COVID‐19 pandemic for chronic pain. Publications were identified related to the COVID‐19 pandemic influence on the burden of chronic pain, development of new‐onset pain because of long COVID with proposed mechanisms and COVID‐19 vaccines and pain interventions. Broadly, mechanisms underlying pain due to SARS‐CoV‐2 infection could be caused by 'systemic inflammatory‐immune mechanisms', 'direct neuropathic mechanisms' or 'secondary mechanisms due to the viral infection or treatment'. Existing chronic pain populations were variably impacted and social determinants of health appeared to influence the degree of effect. SARS‐CoV‐2 infection increased the absolute numbers of patients with pain and headache. In the acute phase, headache as a presenting symptom predicted a milder course. New‐onset chronic pain was reportedly common and likely involves multiple mechanisms; however, its prevalence decreases over time and symptoms appear to fluctuate. Patients requiring intensive support were particularly susceptible to long COVID symptoms. Some evidence suggests steroid exposure (often used for pain interventions) may affect vaccine efficacy, but there is no evidence of clinical repercussions to date. Although existing chronic pain management could help with symptomatic relief, there is a need to advance research focusing on mechanism‐based treatments within the domain of multidisciplinary care.